Clinker & carvel. A mid-16th century wreck find from Terschelling, the Netherlands - Coenen, Thijs; Overmeer, Alice; Vink, Heidi E. (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
During a stormy night on February 12, 2020, a large ship fragment appeared on the North Sea shore of the Dutch island of Terschelling. The timbers turned out to have belonged to a wooden ship, of which the lower strakes were lapstrake built, and the upper strakes were flush-laid. The clinker strakes were interconnected with rivets as well as small wooden plugs, and both clinker and carvel parts were built shell-first. The aim of this paper is to present the latest results of the research, and to place the wreck find in a wider context of European shipbuilding traditions.